STRATEGI PERSAINGAN USAHA RUMAH MAKAN PADANG DILIHAT DALAM PERSPEKTIF MARKETING SYARIAH DI LABUHANBATU SELATAN SUMATERA UTARA (STUDI KASUS PADA RUMAH MAKAN SERBA NIKMAT) - Nena Mariska Siregar; Rahmi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The background of this study is the large number of competitors in the scope of Padang restaurants around South Labuhanbatu so that there is a lack of public interest in Padang restaurant menus because many Padang restaurants still do not understand effective strategies in increasing their sales quantity, the obstacle that occurs is the increase in food prices due to the increase in basic ingredients. This study is a type of field research, this study uses a descriptive-qualitative method, where this study researchers collect data through interviews, observations, and documentation. The data sources used are primary data and secondary data. For data analysis techniques using data reduction, data presentation and drawing conclusions / verification. From the research conducted, it was found that the competitive strategy used by Padang Serba Restaurant uses a marketing mix strategy where the competitive strategy is carried out healthily by prioritizing the quality and service provided to consumers, by excelling in products, prices, promotions, places, and improving the quality of people involved in the business activities so that they are in accordance with the existing process and in accordance with the existing physical evidence.